National Dam Inspection Program. Cooks Pond Dam (NDI I.D. PA-0041 DER I.D. 008-035) Susquehanna River Basin, Tributary of Beaver Creek, Bradford County, Pennsylvania. Phase I Inspection Report. - D'APPOLONIA CONSULTING ENGINEERS INC PITTSBURGH PA (1981)
Based on the evaluation of the existing conditions, the condition of Cooks Pond Dam is considered to be unsafe/nonemergency due to the seriously inadequate spillway capacity and structural deficiencies. The condition of the embankment is considered to be poor. The dam is old and in a general state of disrepair. The crest of the dam is irregular and the center of the dam appears to have settled. The stone wall along the downstream toe is irregular and bulging. The toe of the wall is swampy, caused by a general underseepage. In view of these observations, the overall stability of the dam is considered to be questionable, requiring further investigation and implementation of measures to improve the stability of the dam. The spillway capacity was evaluated according to the recommended procedure and was found to pass less than 10 percent of the Probable Maximum Flood (PMF) without overtopping the embankment. This capacity is less than the required spillway capacity of one-half PMF relative to the size and hazard classification of the dam. Because the spillway capacity is less than 50 percent of the PMF and it is estimated that failure of the dam due to overtopping would significantly increase the downstream hazard of loss of life compared to that which would exist just before failure, the spillway is considered to be seriously inadequate, and consequently the condition of the dam is considered to be unsafe/nonemergency. Original contains color plates: All DTIC/NTIS reproductions will be in black and white.